Self-compassion: no communal alternative to agentic self-esteem - Hauke-Forman, Nicole; Kollmayer, Marlene (Frontiers in Psychology, 2025)
Research on associations of the two fundamental dimensions of self-concept and positive attitudes toward one’s self has primarily focused on self-esteem which has been shown to be dominantly explained by agency and not communion. The present research included self-compassion as an alternative positive self-attitude construct, characterized by self-kindness rather than positive self-evaluations. Based on theoretical considerations and previous results, we expected self-compassion to be equally predicted by communion and by agency. Two studies came to very similar results: Self-compassion was strongly related to agency, especially to its facet assertiveness. In contrast, self-compassion was only weakly related to communion. On the level of self-compassion’s subcomponents, only self-kindness was related to communion, especially to its facet warmth. Self-esteem was most strongly predicted by agency, especially by its facet assertiveness; competence and warmth showed additional weaker predictive power. Thus, self-compassion seems to be an alternative, but no communal alternative to self-esteem.